#1**0 **

I'm going left to right with the multiplication. Q is across the top, E is down the left.\(\left.\begin{matrix} &11&-5i\\ 3&33&-15i\\ -2i&-22i&-10 \end{matrix}\right] = 23 - 37i\).

Now, we multiply QE by D. \((23-37i) \times 2i = QE \times D = QED = 46i + 74\).

Remember, i * i = -1, and -i * i = 1. *i* is effectively a variable until you are dealing with more than one of them being multiplied.

I think the term for this is "abstract quantity"? It's a value you use like a variable with some exceptions.

helperid1839321 Aug 30, 2021